2019
DOI: 10.1080/16549716.2019.1603516
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in early childhood mortality in Myanmar - Association between parents’ socioeconomic status and early childhood mortality

Abstract: Background: Despite global achievements in reducing early childhood mortality, disparities remain. There have been empirical studies of inequalities conducted in low-and middleincome countries. However, there have been no epidemiological studies on socioeconomic inequalities and early childhood survival in Myanmar. Objective: To estimate associations between two measures of parental socioeconomic statushousehold wealth and educationand age-specific early childhood mortality in Myanmar. Methods: Using cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
6
1
Order By: Relevance
“…The results of the analysis informed that the richest group also had a risk of neonatal death, although the number was less than the other groups. This finding contradicts most studies which reveal that the low economic status (poorest, poorer, middle) is more at risk of neonatal mortality [9][10][11] . This information suggests that the economic status of the family, at any level, is likely to increase the risk of neonatal mortality.…”
Section: Resultscontrasting
confidence: 86%
“…The results of the analysis informed that the richest group also had a risk of neonatal death, although the number was less than the other groups. This finding contradicts most studies which reveal that the low economic status (poorest, poorer, middle) is more at risk of neonatal mortality [9][10][11] . This information suggests that the economic status of the family, at any level, is likely to increase the risk of neonatal mortality.…”
Section: Resultscontrasting
confidence: 86%
“… 25 Similar to the results from prior studies including pooled results from a systematic review that assessed the association between caregiver education and all-cause childhood mortality in low- and middle-income countries, we found that low caregiver education was associated with greater risk of childhood mortality. 26 27 Our study adds to the literature as prior studies have not demonstrated an association between caregiver education level specifically following hospital discharge. 3 4 …”
Section: Discussionmentioning
confidence: 60%
“…The explanatory variables were selected based on existing literature regarding predictors of pregnancy loss in Pakistan (7-9, 15, 16, 21, 22). This study also adapted the Mosley and Chen framework which is widely used to study child survival in LMIC (17,(23)(24)(25)(26)(27)(28). The framework consists of community level factors, socioeconomic factors, maternal factors, environmental factors, and health services factors as seen in Fig.…”
Section: Potential Explanatory Variablesmentioning
confidence: 99%